The effect of dietary fat supplements on the activity of palmitic and stearic acid desaturases based on the results of a study of the fatty acid composition of neutral lipids in blood serum and liver of rats receiving a fat-free diet - Levitsky, A.; Gozhenko, A.; Velichko, V.; Selivanskaya, I. (Journal of Education, Health and Sport, 2022)
Background. Desaturase enzymes are involved in the formation of monoenoic acids from saturated fatty acids. One such enzyme is stearyl-CoA-desaturase (SCD1), which converts stearic acid to oleic acid. The aim of this work was to determine the effect of edible fats with different fatty acid compositions on SCD1 activity. Methods. High linoleic sunflower oil (HLSO), high oleic sunflower oil (HOSO) and palm oil (PO) were used. The rats were fed for 30 days with a semi-synthetic diet that did not contain any fats (FFD) and fat diets containing 5 % of each of the above oils. In animals, lipids were extracted from serum and liver and divided into 3 fractions: neutral lipids (NL), phospholipids (PL), and free fatty acids (FFA). The fatty acid composition of each fraction was determined by gas chromatography. The SCD18 activity was determined by the C18:1 n-9/C18:0 ‒ ratio, and the SCD16 activity was determined by the C16:1 n-7/C16:0 ratio. Results. A higher activity of SCD16 and SCD18 was found in the NL fraction, and the activity of SCD18 significantly exceeds that of SCD16. A decrease in the content of C16:0, C16:1 and C18:0 in the NL fraction of the liver and blood serum was shown. The activity of SCD16 in blood serum and liver decreases in rats fed fat diets, while the activity of SCD18 does not decrease, and even increases with the consumption of HOSO. Conclusions. To determine the SCD1 activity, it is advisable to use the C18:1/C18:0 ratio in terms of the level of fatty acids in the NL fraction. Fatty diet inhibits SCD16 activity, and consumption of HOSO increases SCD18 activity.